Gleneagles Hospital Kuala Lumpur / Puteri Sakinah Muhamad Nazari - Muhamad Nazari, Puteri Sakinah (Faculty of Business and Management, 2023)
My industrial training begins at Gleneagles Hospital Kuala Lumpur from 1 March to 15 August. 24 weeks here was a wonderful journey for me. I have gained a lot of knowledge and learned to communicate well, learn to work in a team and I also get experience in how to real works in healthcare. During the internship, I was departing from Marketing and Communication department (Marcom) to get Rm500 as my allowance and also get other benefits. My supervisor was Ms. Ai Lin and I also worked under Ms. Saleha. In this report, I attach my updated resume and also have the company background, mission, vision and care value. As a private hospital that has an experienced consultant, I also list all the specialists in GKL and the service and facilities that have been provided in the GKL. Other than that, I have listed all the marcom and other events I have joined. It was a great experience for me to participate in the event. I also have made SWOT Analysis for GKL based on my observations and discussion with my SV and also other staff. For each SWOT Analysis, I make a recommendation. Lastly, by doing industrial training students will gain a lot of knowledge, learn new skills and experience in real working-life environments.